Glycine differentially improved the growth and biochemical composition of Synechocystis sp. PAK13 and Chlorella variabilis DT025 - Fathy, Wael A.; AbdElgawad, Hamada; Essawy, Ehab A.; Tawfik, Eman; Abdelhameed, Mohamed S.; Hammouda, Ola; Korany, Shereen Magdy; Elsayed, Khaled N. M. (Frontiers in Bioengineering and Biotechnology, 2023)
The potential of microalgae to produce valuable compounds has garnered considerable attention. However, there are various challenges that hinder their large-scale industrial utilization, such as high production costs and the complexities associated with achieving optimal growth conditions. Therefore, we investigated the effects of glycine at different concentrations on the growth and bioactive compounds production of Synechocystis sp. PAK13 and Chlorella variabilis cultivated under nitrogen availability. Glycine supplementation resulted in increased biomass and bioactive primary metabolites accumulation in both species. Sugar production, particularly glucose content, significantly improved in Synechocystis at 3.33 mM glycine (1.4 mg/g). This led to enhanced organic acid, particularly malic acid, and amino acids production. Glycine stress also influenced the concentration of indole-3-acetic acid, which was significantly higher in both species compared to the control. Furthermore, fatty acids content increased by 2.5-fold in Synechocystis and by 1.36-fold in Chlorella. Overall, the exogenous application of glycine is a cheap, safe, and effective approach to enhancing sustainable microalgal biomass and bioproducts production.